2021
DOI: 10.3390/polym13060913
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Polyvinylpyrrolidone-Eggshell Membrane-Reduced Graphene Oxide Nanofibers for Tissue Engineering Applications

Abstract: One of the best methods to prevent wound infection and speed up wound healing is wound dressing based on nanofiber–polymer scaffolds, which have acceptable antimicrobial performance and appropriate skin regeneration capabilities. In this paper, the electrospinning method was applied to synthesize the polyvinylpyrrolidone-acrylic acid hydrogel (PVPA)–eggshell membrane (ESM)–reduced graphene oxide (rGO) nanosheets nanocomposite dressings with different reduced graphene oxide contents (0, 0.5, 1, and 2 wt.%). Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The spectra for GO show a typical broad absorption band at 3525 cm −1 , which is assigned to the stretching vibration of the hydroxyl groups [ 26 ]. The peaks at 1779 cm −1 , 1616 cm −1 , 1220 cm −1 , and 1026 cm −1 corresponded to the C=O stretching vibration in carboxylic groups, bending vibration of hydroxyl and the stretching vibration of epoxide and alkoxy in GO, respectively [ 27 , 28 ]. After the hydrothermal process to obtain GF, the peak intensity at 1779 cm −1 and 1616 cm −1 get decreased, indicating the partially reduction in GO.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra for GO show a typical broad absorption band at 3525 cm −1 , which is assigned to the stretching vibration of the hydroxyl groups [ 26 ]. The peaks at 1779 cm −1 , 1616 cm −1 , 1220 cm −1 , and 1026 cm −1 corresponded to the C=O stretching vibration in carboxylic groups, bending vibration of hydroxyl and the stretching vibration of epoxide and alkoxy in GO, respectively [ 27 , 28 ]. After the hydrothermal process to obtain GF, the peak intensity at 1779 cm −1 and 1616 cm −1 get decreased, indicating the partially reduction in GO.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this challenge, an alternative strategy has been proposed which is based on the dissolution of the CaCO 3 -containing shell by placing the egg into highly acidic solution. The most common are acetic acid, hydrochloric acid (HA) and ethylenediaminetetraacetic acid (EDTA) (Farjah et al 2013, Mensah et al 2021, Sheish et al 2021. Mensah et al (2021) showed that the acid treatment resulted in thicker and more porous membranes compared to the manual stripping.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…Both GO and rGO encourage stem cell proliferation and differentiation while functioning as scaffolds or parts of a scaffold, making them ideal for tissue engineering and regeneration, the various applications of which are listed in Table 5 . While GO and rGO nanoparticles can be incorporated into scaffolds for general tissue engineering, such as skin [ 188 190 ], cartilage [ 191 , 192 ], bone [ 189 , 193 195 ], and muscle tissue [ 196 , 197 ] rGO is commonly incorporated into nanofibers to enhance their electroconductivity, which is a significant factor in cardiac and nerve tissue regeneration [ 39 41 ]. Tissue engineering applications can also implement GO/rGO for morphological [ 198 ] and photoelectric [ 199 ] stimulations to encourage cell proliferation/differentiation.…”
Section: Applications Of Graphene Oxide- and Reduced Graphene Oxide-b...mentioning
confidence: 99%